Making CHASE Mainstream - DeLine, Robert; DeLIne, Robert (2009)
For the last several decades, various provocateurs have been goading the software engineering research community to take "people issues" seriously. In 1995 we saw the 20th anniversary edition of Brooks' The Mythical Man-month, primarily about human issues in productivity. ICSE 2007 celebrated the 20th anniversary of DeMarco and Lister's Peopleware, an influential book entirely dedicated to human issues, like interruption and coordination. Yet, "people issues" have never been a mainstream research topic in software engineering. (Of ICSE 2009's 50 research track papers, 14 are about people issues, a record number.) In this talk, I'll describe some historical roadblocks to research in this area and some recent trends that are helping to clear them. I'll also suggest some key open problems and bridging techniques that could help bring more researchers into the fold.
CHASE Workshop - Keynote